Improving Literacy Programs as an Effort to Fulfill the Right to Reading Materials for Prisoners at the Class IIB Sukadana State Prison - Edo Prihantoro (Penerbit Hellow Pustaka, 2025)
Development in the field of education in Indonesia has currently provided a form of expansion so that the concept of education itself has a useful access to eradicate illiteracy which can have significant benefits. . This study uses a research design in the form of a descriptive case study where all conclusions will be described in the form of a description that is linked to theory and findings. Case Study is a series of scientific activities carried out intensively and in depth about a program, event, and activity, both at the individual level, a group of people, institutions, or organizations to gain in-depth knowledge about the event. The discussion in this study will basically discuss the results of the researcher's findings during the field to collect primary data in compiling a scientific paper in the form of a thesis. To discuss the problems in this study, the information or data obtained can be adjusted to the existing theory, namely related to library management. In the form of an effort to implement a literacy program, of course, the library is important to achieve the goals of the Literacy program. The results and discussion of this study are the improvement of the literacy program in an effort to fulfill the right to reading materials for prisoners in the Class IIB Sukadana Detention Center using management theory. The Correctional System in this case has an important role in social reintegration efforts where in the correctional efforts to implement a good correctional system, it is necessary to fulfill the rights of prisoners in carrying out their sentences in prisons or detention centers in Indonesia. The Literacy Program is one form of effort made by the Class IIB Sukadana Prison in fulfilling the rights of these prisoners. However, in the implementation process, this Literacy Program did not run well due to obstacles so that innovation is needed to make the implementation of this program run well in the Class IIB Sukadana Prison.